Do climate-related disasters cause dissatisfaction with environmental policies? - Michael Berlemann; Silke Bumann; Joel Methorst (Hamburg Institute of International Economics (HWWI), 2024)
Climate policies need public support to be successfully implemented as they typically come with short-term costs, whereas their revenues accrue far in the future. We study whether the occurrence of climate-related natural disasters have a systematic impact on dissatisfaction with actual environmental policies. Based on geo-referenced worldwide survey data we find robust empirical evidence in favor of the hypothesis that the experience of heatwaves, tropical storms and flood events trigger environmental policy dissatisfaction, at least when controlling for disaster severity. Thus, climate-related natural disasters, which will occur either more often or gain in severity in the course of global warming might significantly contribute to a rising public demand for more effective environmental and climate policies. However, the effect turns out to diminish over time. – – Klimapolitische Maßnahmen benötigen dringend öffentliche Unterstützung, um erfolgreich umgesetzt werden zu können. Dies liegt vor allem daran, dass sie in der Regel mit kurzfristigen Kosten verbunden sind, während ihre Einnahmen weit in der Zukunft anfallen. Wir untersuchen, ob das Auftreten von klimabedingten Naturkatastrophen einen systematischen Einfluss auf die Unzufriedenheit mit der aktuellen Umweltpolitik hat. Auf der Grundlage georeferenzierter weltweiter Umfragedaten finden wir robuste empirische Belege für die Hypothese, dass die Erfahrung von Hitzewellen, tropischen Stürmen und Überschwemmungen die Unzufriedenheit mit der Umweltpolitik auslöst, zumindest wenn man für die Schwere der Katastrophe kontrolliert. Demnach könnten klimabedingte Naturkatastrophen, die im Zuge der globalen Erwärmung entweder häufiger auftreten oder an Schwere zunehmen werden, wesentlich zu einer steigenden öffentlichen Nachfrage nach einer effektiveren Umwelt- und Klimapolitik beitragen. Allerdings nimmt dieser Effekt mit der Zeit ab.
Keywords: 330; policy preferences; natural disasters; climate policy; environment; Gallup World Poll